USER ACCEPTANCE OF CYBER SECURITY APPLICATION (OUR CYBERHERO) AMONG SECONDARY SCHOOL STUDENTS, TEACHERS AND LOCAL COMMUNITIES IN COASTAL TERENGGANU DISTRICT: A PRELIMINARY STUDY FOR MARITIME EDUCATION - MOHD NOOR, MARHAINI; HJ. JOHAN SHAH, MOHAMED AIMAN SHAH; MOHD ZAMRI, NUR SYAHZANANI HANI (Journal of Maritime Logistics, 2022)
This paper is based on knowledge transfer program to improve cyber security awareness among the coastal community in Kuala Terengganu with the use of Our CyberHero application. Thus, this paper introduces the application and adapt Technology Acceptance Model in maritime education settings. A series of these knowledge transfer programs can to some extent address this knowledge gap. This research has conducted a survey to the 59 coastal communities in Terengganu District. This program is a pilot project to the cyber security application Our CyberHero and is divided into two phases. The first phase was held a webinar on the importance of cyber security sustainability in today’s society. While the second phase gives exposure to the use of cyber security applications. This involves collaboration from the Educational Resources and Technology Sector, the Terengganu State Education Department, the Communications and Multimedia Commission and Cybersecurity Malaysia. The stakeholders involved were 24 high school students, 12 teachers and 23 communities from the coastal state of Terengganu. All 36 stakeholders are made up of 12 secondary schools that were selected as pioneers for the knowledge transfer program. Thus, the 23 other communities are besides the school children and the teachers. Acceptance of the use of cyber security application is very encouraging among students and teachers of coastal secondary schools in the Terengganu district. The 85% of the users feel easy to use the application as the module is easy to understand and friendly user. Therefore, the users feel confidence to use and share information widely (65%). With the high confidence level and understanding of the application, the users tend to trust the application system and the other users (59%). As a result, 57% users are intended to use Our CyberHero application and 52% of the users also feel the application is useful.